Comparison Analysis of Bubble Sort Algorithm with Tim Sort Algorithm Sorting Against the Amount of Data - Muhammad Rizal Hanafi; Muhammad Azfa Faadhilah; Muhammad Taufik Dwi Putra; Deden Pradeka (Universitas Pendidikan Indonesia, 2022)
The role of algorithms in software or programming is so important that you need to understand the basic concepts behind them. In most of our daily life, we often face problems that need to be solved by entering the data sorting process. A lot of programming logic has been created, both in the general case and in the special case. In this study, the authors carried out the sorting process with two methods, namely bubble sort and tim sort. Sorting application is built using C++ program. Algorithms are needed in order to be able to solve a problem more effectively and efficiently in a shorter time using only a few resources. The preparation of this research uses data collection methods that aim to obtain the necessary data so that it can be extracted to be used as information. It is hoped that from this information it can be seen that the comparison of the bubble sort algorithm with the tim sort is getting better in the data sorting process, if the number of inputted data is greater than n.